2014
DOI: 10.1186/1477-7819-12-194
|View full text |Cite
|
Sign up to set email alerts
|

Primary synovial sarcoma of the prostate metastatic to the liver and lung: a case report

Abstract: Primary synovial sarcoma of the prostate is an uncommon malignant tumor. There are few cases reported in the English medical literature to date. Here, we present a case of 22-year-old man with primary synovial sarcoma of the prostate metastatic to the liver and lung. To our knowledge, only six reports of synovial sarcoma involving the prostate have been previously published. We also reviewed the previous treatments and prognoses in previous case reports and evaluate the proper treatment for this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…20 Review of reported cases of prostatic synovial sarcoma demonstrates variable prognosis. 3,4,7 Interestingly, the mean age of the patients who died of disease was slightly lower (35 versus 51) and their mean tumor size was larger (11.4 cm versus 6.7 cm). 3,4,7 Interestingly, the mean age of the patients who died of disease was slightly lower (35 versus 51) and their mean tumor size was larger (11.4 cm versus 6.7 cm).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…20 Review of reported cases of prostatic synovial sarcoma demonstrates variable prognosis. 3,4,7 Interestingly, the mean age of the patients who died of disease was slightly lower (35 versus 51) and their mean tumor size was larger (11.4 cm versus 6.7 cm). 3,4,7 Interestingly, the mean age of the patients who died of disease was slightly lower (35 versus 51) and their mean tumor size was larger (11.4 cm versus 6.7 cm).…”
Section: Discussionmentioning
confidence: 98%
“…[3][4][5][6][7][8] The age range is 22-63 with a mean of 43 years. Apart from our case there have been only seven reported cases of prostatic synovial sarcoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumors ranged in size from 4 to 15 cm, with a mean size of 9.9 cm in greatest dimension. [7][8][9][10][11][12][13] HISTOPATHOLOGY Not surprisingly, intraprostatic synovial sarcoma histologically mirrors those found elsewhere in the body. However, to the best of our knowledge only the biphasic and monophasic fibrous types have been described in the English literature to date.…”
Section: Macroscopic Findingsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Of these, the mean age at time of diagnosis is 42 years old, with an overall age range of 28 to 63 years. It typically presents with nonspecific lower urinary tract symptoms, including dysuria, increased urinary frequency, and nocturia.…”
Section: Clinical Featuresmentioning
confidence: 99%